1994
DOI: 10.1093/bja/73.4.559
|View full text |Cite
|
Sign up to set email alerts
|

Postal survey of paediatric practice and training among consultant anaesthetists in the UK

Abstract: A postal survey of previous paediatric anaesthetic training, current paediatric experience and management of an infant pyloromyotomy was undertaken among consultant anaesthetists in the UK. A total of 851 questionnaires were returned, giving a response rate of 31%; 352 (41%) consultants had at least one paediatric list each week, 180 (21%) anaesthetized more than one infant less than 6 months old each month and 373 (44%) had obtained more than 6 months' specialist training. Consultants trained most recently ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…[20] The results of surveys from the United Kingdom indicated that RSI was modified more frequently for infants. [21] Cricoid pressure would include hyperextension of the neck with placement of a hard neck rest beneath the cervical curve, which may not be applicable due to the small size of the child. In the literature, several publications refer to a MRSI with the use of inhalation induction[2223] and RSI after pre-loading with narcotics[2425] or without the use of muscle relaxants.-[26] In this survey, 33% of respondents would consider a MRSI without administration of muscle relaxant when concerned about a muscular pathology [Figure 4].…”
Section: Discussionmentioning
confidence: 99%
“…[20] The results of surveys from the United Kingdom indicated that RSI was modified more frequently for infants. [21] Cricoid pressure would include hyperextension of the neck with placement of a hard neck rest beneath the cervical curve, which may not be applicable due to the small size of the child. In the literature, several publications refer to a MRSI with the use of inhalation induction[2223] and RSI after pre-loading with narcotics[2425] or without the use of muscle relaxants.-[26] In this survey, 33% of respondents would consider a MRSI without administration of muscle relaxant when concerned about a muscular pathology [Figure 4].…”
Section: Discussionmentioning
confidence: 99%
“…Despite a clear inverse relationship between complications in paediatric anaesthesia and the number of anaesthetics administered, determining a minimum case volume is difficult. Nevertheless, Auroy et al [53,54] recommend a minimum of 200 cases annually.…”
Section: The Paediatric Anaesthesia Teammentioning
confidence: 99%
“…In 1997 Auroy et al showed that groups performing fewer than 100 paediatric anaesthetic procedures a year had a significantly increased complication rate compared with groups performing more than 200 procedures 17. Stoddart identified that a major problem of occasional paediatric anaesthetic practice is for the anaesthetist to remain up to date 18. There is broad agreement with this general philosophy19 20; however, it is not happening in practice as shown by the Digivote survey conducted by the Association of Anaesthetists Linkman Conference in 1996—only 60% of hospitals providing paediatric anaesthesia complied with the Royal College of Anaesthetists’ guidelines,21 22 and most disturbing of all only 62% of those present would be happy to allow their own children to be anaesthetised in their own hospital under its current arrangements 20…”
Section: The Specialist Paediatric Surgical Centrementioning
confidence: 99%
“…Training is also highlighted as a problem in other allied specialities such as paediatric intensive care40 and anaesthesia 18…”
Section: Trainingmentioning
confidence: 99%